1993
DOI: 10.4148/2378-5977.6376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat gluten and plasma protein on growth performance and digestibility of nutrients in nursery pigs (1993)

Abstract: An experiment was conducted to determine the nutritional value of wheat gluten and spray-dried porcine plasma in diets for weanling pigs. For the experiment, 120 pigs (14 lb avg initial body wt) were used in a 35-d growth assay. Treatments fed from d 0 to 14 postweaning were: 1) a dried skim milk-dried whey-soybean mealbased control; and 2, 3, and 4) spray-dried wheat gluten, spray-dried porcine plasma, and a blend of the wheat gluten and porcine plasma used to replace dried skim milk on a protein basis. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, no effects of SDPP supplementation in broiler diets were previously reported on ileal digestibility of DM, CP and GE (Beski et al, 2015b; Jamroz et al, 2012), despite weak differences in digestibility of EE (Jamroz et al, 2012). No effects of different inclusion levels of SDPP have been reported for the total apparent digestibility coefficient of CP in weanling pigs by Sun, Ma, Li, and Ji, (2009), whereas other authors found higher DM and CP digestibility for SDPP compared to other protein sources in young pigs (Pendergraft, Hancock, Hines, Mills, & Burnham, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…However, no effects of SDPP supplementation in broiler diets were previously reported on ileal digestibility of DM, CP and GE (Beski et al, 2015b; Jamroz et al, 2012), despite weak differences in digestibility of EE (Jamroz et al, 2012). No effects of different inclusion levels of SDPP have been reported for the total apparent digestibility coefficient of CP in weanling pigs by Sun, Ma, Li, and Ji, (2009), whereas other authors found higher DM and CP digestibility for SDPP compared to other protein sources in young pigs (Pendergraft, Hancock, Hines, Mills, & Burnham, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…The observed increase in ATTD of N in diets containing SDP compared with diets without SDP agrees with data from mice and pigs ( Thomson et al, 1995 ; Pan et al, 2019 ). An increase in ATTD of dry matter and N was also observed if SDP was included in a diet fed to pigs compared with a diet containing wheat gluten ( Pendergraft et al, 1993 ). The improvement in N digestibility and retention by pigs fed a SDP-containing diet is due to the high bioavailability and digestibility of amino acids in SDP ( Mateo and Stein, 2007 ; Almeida et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%